Les lampes de Montans (Tarn) Une production céramique des Ier et IIe s. ap. J.-C. : modes de fabrication, typologie et chronologie - Bergès, Gabrielle (Documents d'archéologie française, 1989)
For about ten years numerous studies have been carried out in France about roman lamps. This one, for the first time and for a masters' degree research, is oriented toward the systematic study of productions from several potters' workshops in Montans (Tarn), ail from welldated archaeological context. More than a simple descriptive inventory, the author gives us a chronology of the Ist and IInd centuries. Her analysis of three associated criteria (decoration/type/sig nature, mark), based upon the study of 900 pieces, reveals some original aspects of the potters' practice and leads to interesting interpretations about the technique used most of the time in Montans which consists in making moulds from lamps already in use.